2013
DOI: 10.1002/bjs.9279
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical and functional outcome following treatment for Paget–Schroetter syndrome

Abstract: Patients treated surgically for PSS had better functional outcomes than those managed conservatively. Prompt thrombolysis and surgery was superior to delayed management with respect to rethrombosis and functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…The two modalities of treatment were compared in 117 patients diagnosed with PSS [ 7 ]. In that study, Taylor and colleagues concluded that patients treated surgically had better outcomes than those treated with CDT alone.…”
Section: Discussionmentioning
confidence: 99%
“…The two modalities of treatment were compared in 117 patients diagnosed with PSS [ 7 ]. In that study, Taylor and colleagues concluded that patients treated surgically had better outcomes than those treated with CDT alone.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of clot dissolution ranging from 62% to 82% have been reported by various authors depending on the duration of symptoms. [29][30][31] However, the rate of successful thrombolysis after 14 days or more of symptoms is significantly decreased. Molina reported only a 29% success rate in patients treated 2-12 weeks after symptom development.…”
Section: Treatmentmentioning
confidence: 99%
“…105 This risk decreases to 2% when multimodality therapy (anticoagulation, thrombolysis, and surgical decompression) is used to treat patients. 106 In the long term, the most significant complication is the development of PTS. Although the risk of PTS in children with vTOS is not well studied, a recent retrospective Canadian study of 23 children with primary upper extremity DVT found that 87% of patients had mild to moderate PTS symptoms at a median follow-up of 1.6 years.…”
Section: Special Considerations: Anatomic Predisposition Syndromesmentioning
confidence: 99%